Semantic features of the political opponent nomination as a way of his discreditation (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with evaluative nomens semantic features to describe political opponents, identifies the most frequent semes, updated in the process of such nomination, their role in the deployment the strategy of the discreditation of a nomination object.
Keywords: the nomination; the strategy to discredit; a verbal aggression